2000
DOI: 10.1046/j.1365-2796.2000.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of coronary heart disease with age‐adjusted aortocoronary calcification in patients with familial hypercholesterolaemia

Abstract: Abstract. Jensen JM, Gerdes LU, Jensen HK, Christiansen TM, Brorholt-Petersen JU, Faergeman O (Aarhus Amtssygehus University Hospital, Aarhus, Denmark). Association of coronary heart disease with age-adjusted aortocoronary calcification in patients with familial hypercholesterolaemia. J Intern Med 2000; 247: 479±484.Objectives. Existing algorithms of risk of coronary heart disease (CHD) do not pertain to patients with familial hypercholesterolaemia (FH), whose arteries have been exposed to hypercholesterolaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146). Associations of calcium/phosphorus/parathyroid hormone dysregulation with CVD and concerns that coronary artery calcification may beget coronary artery occlusive disease (147)(148)(149)(150) argue for an important role of VC in the CVD epidemic in ESRD (84,151).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…VC is probably primarily due to abnormal mineral metabolism that is seen in renal failure (141)(142)(143)(144)(145), perhaps through a complex process involving osseous metaplasia of the vascular wall components (118,119,146). Associations of calcium/phosphorus/parathyroid hormone dysregulation with CVD and concerns that coronary artery calcification may beget coronary artery occlusive disease (147)(148)(149)(150) argue for an important role of VC in the CVD epidemic in ESRD (84,151).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…Arterial wall calcification is common in patients with familial hypercholesterolemia, a genetic disorder of cholesterol metabolism. [3][4][5] Several studies have identified the relationship between the serum level of low-density lipoprotein cholesterol (LDL-C) and arterial wall calcification; moreover, lipid-lowering therapy using 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors has been reported to inhibit the progression of arterial wall calcification. 6,7 In patients receiving long-term hemodialysis, elevated serum triglyceride (TG) levels and reduced high-density lipoprotein cholesterol (HDL-C) levels are risk factors for coronary artery calcification.…”
mentioning
confidence: 99%
“…Most of the previous studies used the "calcium score" determined by CT as a semiquantitative index of calcification of the aorta or coronary arteries. [3][4][5][6][7] However, the calcium score may not accurately reflect subtle changes in calcium deposit levels. To accurately quantify the degree of calcium deposition, we developed an image color analysis software program that can automatically determine the percentages of calcified volume against whole vascular volume (%ACV) using plain CT. 9 We previously reported a strong correlation between %ACV and aortic calcification dimension in aortas of autopsy specimens, the latter of which was determined using soft X-ray photographs.…”
mentioning
confidence: 99%
“…Jensen et al found that age-adjusted calcium scores still increased slightly with age, suggesting that coronary calcification is a self-perpetuating process 12) . His diagnostic model for the prediction of CAD in FH patients based on cholesterol-year scores was the weakest model in his study, more than his model based on a combination of traditional risk factors, including age, sex, smoking, hypertension, untreated cholesterol, and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…CCS is recommended to estimate the risk of coronary events in asymptomatic individuals, particularly those with intermediate risks, but high prognostic and diagnostic values were also shown in high-risk patients 10) . To date, only a few studies are available that report about CCS in patients with FH [11][12][13] . percutaneous transluminal coronary angioplasty, angina, wall motion abnormalities on an echocardiogram, or positive results of exercise testing which was performed on all patients with results of CCS above 100.…”
Section: Introductionmentioning
confidence: 99%